Psychotherapy of generalized anxiety disorder - S. V. Jargin (Сибирский научный медицинский журнал, 2024)
Generalized anxiety disorder is characterized by persistent, poorly controlled anxiety and fears for various reasons. Thoughts are dominated by the themes of danger. Nonspecific symptoms include tension, restlessness, fatigue, poor concentration, irritability and dysautonomia. In the long run, the risk of depression and alcoholism is increased, comorbidity with affective, addictive and other disorders is often encountered. The article provides a brief overview of psychotherapy methods for this disorder. The cognitive behavioral psychotherapy appears to be most effective. One of the main goals of the therapy is training of realistic and objective thinking. Using self-observation, the patient becomes aware of his tendency to seek out and exaggerate threats. The problem-solving training can be used to improve social competence and coping skills. Various relaxation methods and other varieties of psychotherapy are applied. The schema therapy is an integrative approach including elements of different methods. Internet counseling can be used in isolation or as an adjunct to conventional psychotherapy. Anxiety disorders were diagnosed relatively rarely in Russia, and the number of psychotherapists was smaller than in other developed countries. Today, the situation is changing thanks to success of psychotherapy and development of individual rehabilitation regimes.